143k views
4 votes
What is the sum of first k+1 even numbers

User Joe Morgan
by
5.8k points

1 Answer

5 votes

Answer:


Sum = (k+1)(k+2)

Explanation:

Given

k + 1 even numbers

Required

Their sum

This question will be solved using the sum of nth term of an AP


S_n = (n)/(2)(2a + (n - 1)d)

Where

a = the first even number


a = 2

n = number of terms


n =k +1

d = difference between consecutive even numbers


d = 2

So, the expression becomes:


Sum = (k+1)/(2)(2 * 2 + (k + 1 - 1) * 2)


Sum = (k+1)/(2)(2 * 2 + (k) * 2)


Sum = (k+1)/(2)(4 + 2k)


Sum = ((k+1)(4 + 2k))/(2)

Factorize 4 + 2k


Sum = ((k+1)*2*(2 + k))/(2)


Sum = (k+1)*(2 + k)


Sum = (k+1)*(k+2)


Sum = (k+1)(k+2)

User ConnorU
by
6.4k points